Different drinking motives, different adverse consequences? Evidence among adolescents from 10 European countries. (5th June 2017) - Wicki, Matthias; Kuntsche, Emmanuel; Eichenberger, Yvonne; Aasvee, Katrin; Bendtsen, Pernille; Dankulincová Veselská, Zuzana; Demetrovics, Zsolt; Dzielska, Anna; Farkas, Judit; de Matos, Margarida Gaspar; Roberts, Chris; Tynjälä, Jorma; et al.
Abstract: Introduction and Aim. This study, which builds on previous research demonstrating that drinking motives are associated with adverse consequences, investigates the associations between drinking motives and non‐alcohol‐attributed adverse consequences and disentangles alcohol‐related and direct effects.Design and Method. On the basis of a sample of 22 841 alcohol‐using 13‐ to 16‐year‐olds (50.6% female) from Belgium, Denmark, Estonia, Finland, Ireland, Portugal, Scotland, Slovakia, Switzerland and Wales, structural equation models were used to estimate direct and indirect effects. Additionally, differences across countries were tested in a multigroup analysis.Results. The indirect effect (via alcohol use) was greater for injuries and academic problems than for more general outcomes such as life dissatisfaction and negative body image. For social, enhancement and coping motives, we found positive indirect effects (via alcohol use) on injuries and academic problems; the association was negative for conformity motives. The direct effect, that is, the effect above and beyond alcohol use, indicated more negative consequences among those who tended to drink more frequently for coping motives. More negative consequences, such as injuries and negative body image, were also found among those who drink for conformity motives. The pattern of association was largely comparable across countries.Discussion and Conclusion. While the actual mean level of drinking motives, alcohol use and adverse consequence varied across countries, the consistency of association patterns implies that drinking motive‐inspired health promotion efforts are likely to be beneficial across Europe. This is particularly important for coping drinkers because they are especially prone to adverse consequences over and above their alcohol use. [Wicki M, Kuntsche E, Eichenberger Y, Aasvee K, Bendtsen P, Dankulincová Veselská Z, Demetrovics Z, Dzielska A, Farkas J, de Matos MG, Roberts C, Tynjälä J, Välimaa R, Vieno A. Different drinking motives, different adverse consequences? Evidence among adolescents from 10 European countries.